Epidemiology of Burn Cases in Erbil Governorate (Medico Legal Update, 2020)
Background and Objectives: Management and prevention of burns are done through epidemiologicalstudy. The mortality rate of burn injuries is seven times higher in the low income countries than the highincome countries. The aim of this research was to study the epidemiology of burn injury cases throughanalysis of the cause, magnitude and profile of burn in Erbil governorate as a method for planning preventiveand management strategies.Method: A retrospective study was conducted on 593 burn cases to assess the epidemiology of burn injurycases in Erbil Governorate the capital of Iraqi Kurdistan Region from 2012 to the end of 2016. Descriptiveand inferential statistics were used through the Microsoft Excel Database and the Statistical Package forSocial Sciences (SPSS, Version 24). The P value of > 0.05 was considered as non-statistically significant.The P value of ? 0.05 was considered as statistically significant. The P value of ? 0.01 was considered ashighly statistically significant.Results: The total number of burn cases in Erbil governorate during the period 2012 to 2016 was 593 victims.The mean (±SD) age of the studied cases was 26 ± 10.9 years ranging from one to 82 years. The highestnumber 189 (31.9%) of registered burn cases was in 2013, while the lowest number 74 (12.5%) of caseswas in 2015. The female to male ratio of the burn victims was 2.1:1. More than half (56.7%) of them weremarried, while the others (43.3%) were single. Husband and polygamy were the highest leading causes ofthe burn cases in a way that each of the causes had formed 18.4% of the cases. The highest number (44.35%)of the burn cases was among the age group 21 to 30 years. There was a significant correlation between themarital status of the studied cases with the causes behind the burn injuries at p = 0.027 and highly significantcorrelation of the marital status with the survival rates in. The correlation was highly significant between thegender of the studied samples and the cause of the burns. There was no significant correlation between theeducational levels of the burn victims with the causes and the survival rates as well.